A study of Malaysian art and culture to be applied on skateboard deck design / Muhammad Amirullah Zainor - Zainor, Muhammad Amirullah (2015)
Of all the extreme sports that made their way to Malaysia, skateboarding has the biggest success in a short time among the public. Skateboarding has been a popular sport for the past 3 decades, and is quite modem. In fact, skateboarding has been around since 1980, which happens to be the year in which the first modem skateboard was made. Since then, both young and the not so young enjoy carving the streets and experiencing the adrenaline rush of free riding, trick skating and the like. Skateboarding is deeply influenced by and derivative of the art and sport of surfing. Surfing, which was developed and rooted in Hawaii, is the act of riding waves with a surfboard. Similar to surfing, skateboarding entails riding a skateboard on land, and more specifically, paved or concrete surfaces. Skateboards are made in different styles and made with different skating methods in mind. Some skateboards are styled and fashioned after longboard surfboards. While these skateboards are not intended for extensive tricks, longboard skateboards are great for bombing hills and carving while you cruise the streets.